Applying the Cloud Intelligent Classroom to the Music Curriculum Design of the Mental Health Education - Liang, Yanan; Wu, Shiyong (Frontiers in Psychology, 2021)
The cloud intelligent classroom, supported by modern technologies, is the main trend of curriculum design in the future. The purpose of this study is to explore the promotion and integration between digital technology and the curriculum of mental health education in colleges and universities and realize their real value. First, the overall idea and practical value of the study are clarified after the relevant literature is reviewed. Second, the setting, the teaching methods, and the ideas of the cloud classrooms based on digital technology are elaborated in detail. Then, the final effect of mental health education in cloud intelligent classrooms is demonstrated and summarized after the teaching practice, a questionnaire survey, and expert assessment. Finally, the research conclusions are drawn, and the suggestions for constructing cloud intelligent classrooms of mental health education are proposed based on practice and surveys. The research is based on the reality of mental health education in colleges and universities, rational thinking, and action. While updating the means and methods of mental health education curriculum in senior high school, it expands the connotation of cloud intelligent curriculum and pursues the unity of "form" and "content". The cloud intelligent classroom helps to improve the teaching quality of mental health education for music majors in colleges and universities in the short term. And cloud intelligent classrooms can help to achieve the curriculum design and teaching objectives.